2008
DOI: 10.1007/s11104-008-9560-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azospirillum brasilense indole-3-acetic acid production on inoculated wheat plants

Abstract: The production of phytohormones by plantgrowth promoting rhizobacteria is considered to be an important mechanism by which these bacteria promote plant growth. In this study the importance of indole-3-acetic acid (IAA) produced by Azospirillum brasilense Sp245 in the observed plant growth stimulation was investigated by using Sp245 strains genetically modified in IAA production. Firstly wildtype A. brasilense Sp245 and an ipdC knock-out mutant which produces only 10% of wild-type IAA levels (Vande Broek et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(94 citation statements)
references
References 34 publications
(22 reference statements)
4
79
0
4
Order By: Relevance
“…When root exudates decrease and become a limiting factor for bacterial growth, bacterial production of IAA increases, thereby triggering lateral root and root hair formation. A. brasilense Sp245, which produces IAA, increased leaf length and shoot dry weight of spring wheat compared to a non-inoculated control (Spaepen et al 2008). Aeromonas spp., A. brasilense, and Comamonas acidovorans are among the many IAA species that promote plant growth in rice (Oryza sativa) (Mehnaz et al 2001), wheat (Kaushik et al 2000), and lettuce (Lactuca sativa) (Barazani and Friedman 1999).…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 97%
See 1 more Smart Citation
“…When root exudates decrease and become a limiting factor for bacterial growth, bacterial production of IAA increases, thereby triggering lateral root and root hair formation. A. brasilense Sp245, which produces IAA, increased leaf length and shoot dry weight of spring wheat compared to a non-inoculated control (Spaepen et al 2008). Aeromonas spp., A. brasilense, and Comamonas acidovorans are among the many IAA species that promote plant growth in rice (Oryza sativa) (Mehnaz et al 2001), wheat (Kaushik et al 2000), and lettuce (Lactuca sativa) (Barazani and Friedman 1999).…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 97%
“…Many different bacterial species can produce IAA through various mechanisms. For example, (Spaepen et al 2008) found that IAA production by A. brasilense was regulated by root exudates. When root exudates decrease and become a limiting factor for bacterial growth, bacterial production of IAA increases, thereby triggering lateral root and root hair formation.…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 99%
“…IAA-producing Azospirillum sp. also promoted alterations in the growth and development of wheat (Triticum aestivum L.) plants [69][70][71][72]. Bacteria of the Azotobacter genus synthesize auxins, cytokinins and GA-like substances, and these growth materials are the primary substances controlling the enhanced growth [73].…”
Section: Production Of Plant Hormones and Other Beneficial Plant Metamentioning
confidence: 99%
“…IAA synthesis by these bacteria is reported to be affected by tryptophan, vitamins, salt and oxygen levels, as well as pH, temperature, carbon and nitrogen source. For example, IAA from Azospirillum brasilense Sp245 stimulates early plant development and increases significantly the plants and roots yield (in dry weight) and the N-uptake efficiency of wheat [71,80]. The ability to synthesize ABA, particularly under stressful conditions, for example, salinity, and to affect the ABA level in plants was detected in PGPB from the genera Azospirillum, Bacillus, Pseudomonas, Brevibacterium and Lysinibacillus [15,81,82].…”
Section: Production Of Plant Hormones and Other Beneficial Plant Metamentioning
confidence: 99%
“…Successful inoculation results in changes the root morphology and phytohormonal balance which are also attributed to successful inoculation [16]. A. brasilense Sp245 inhibits root growth of wheat, whereas the root length is recovered as similar length to control when a mutant strain lacking indole acetic acid (IAA) productivity is inoculated [17]. These results suggest that the effect on root growth is due to IAA produced by A. brasilense Sp245.…”
Section: Introductionmentioning
confidence: 99%